Removal lead (Pb) and mercury (Hg) from juaro fish (Pangasius polyuranodon) using citric acid from pineapple extract (Ananas comosus) as chelating agent - Pra Dian Mariadi; Rosnita Sebayang (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
An assessment of dietary risk of heavy metals exposure to human is important since it is the main of exposure. The aim of study to measure the contamination of lead and mercury in juaro fish meat and the effort to reduce contaminations using citric acid from pineapple extract as a chelating agent. Samples was soaked and boiled in citric acid extract at concentration 50%, 75 %, 100 % for, 15 min, 30 min, 45 min at 25 0C, 50 0C and 100 0C. The concentration of lead and mercury in Juaro fish lower than the maximum acceptable lever for Pb and Hg respectively (1mg/kg for Pb, 0,5 mg/Kg for Hg). The result indicated that after soaking and boiling in citric acid solution form pineapple extract at concentration 100 % for 45 min at 100 0C reducing heavy metals Pb from 0,02 mg.Kg-1 to 0,003 mg.Kg-1 and Hg from 0,011 mg.Kg-1 to lower than 0,0001 mg.Kg-1. The increasing of soaking time and boiling temperature, the levels of Pb and Hg in Juaro fish Tissue will decreasing.